B-type natriuretic peptide as a marker of heart failure: new insights from biochemistry and clinical implications. (April 2010) - Vanderheyden, Marc; Vrints, Chris; Verstreken, Sofie; Bartunek, Jozef; Beunk, Jan; Goethals, Marc
The mature, biologically active 32-amino acid long B-type natriuretic peptide (BNP1–32 ), is cleaved by corin from the BNP prohormone. Recent data demonstrated that BNP1–32 might be an ideal substrate for the endogenous aminopeptidase, dipeptidyl-peptidase (DPP) IV. DPP IV removes the two amino-terminal amino acids (Ser and Pro) from BNP1–32 to produce BNP3–32, which has been detected in plasma of patients with heart failure. In a canine model, intravenous BNP3–32 infusion resulted in less natriuresis, diuresis and vasodilation compared to intravenous infusion of BNP1–32 . The clinical relevance of these observations may be important for patients with high plasma BNP concentrations, which can be measured by commercially available immunoassays. Further studies are needed to explore whether DPP IV inhibitors increase the bioavailability of BNP1–32, delay the progression of heart failure and increase the efficacy of exogenously administered BNP1–32 in decompensated heart failure.